Contact conditions for total hip head-neck modular taper junctions with microgrooved stem tapers. (16th April 2020) - Bechstedt, Maren; Gustafson, Jonathan A.; Mell, Steven P.; Gührs, Julian; Morlock, Michael M.; Levine, Brett R.; Lundberg, Hannah J.
Abstract: Implant failure due to fretting-corrosion of head-neck modular junctions is a rising problem in total hip arthroplasty. Fretting-corrosion initiates when micromotion leads to metal release; however, factors leading to micromotion, such as microgrooves on the stem taper, are not fully understood. The purpose of this study is to describe a finite element analysis technique to determine head-neck contact mechanics and investigate the effect of stem taper microgroove height during head-neck assembly. Two-dimensional axisymmetric finite element models were created. Models were created for a ceramic femoral head and a CoCrMo femoral head against Ti6Al4V stem tapers and compared to available data from prior experiments. Stem taper microgroove height was investigated with a generic 12/14 model. Head-neck assembly was performed to four maximum loads (500 N, 2000 N, 4000 N, 8000 N). For the stem taper coupled with the ceramic head, the number of microgrooves in contact and plastically deformed differed by 2.5 microgrooves (4%) and 6.5 microgrooves (11%), respectively, between the finite element models and experiment. For the stem taper coupled with the CoCrMo head, all microgrooves were in contact after all assembly loads in the finite element model due to an almost identical conical angle between the taper surfaces. In the experiments, all grooves were only in contact for the 8000 N assembly load. Contact area, plastic (permanent) deformation, and contact pressure increased with increasing assembly loads and deeper microgrooves. The described modeling technique can be used to investigate the relationship between implant design factors, allowing for optimal microgroove design within material couples.